Incorporating stakeholder perspectives into model-based scenarios: Exploring the futures of the Dutch gas sector. (October 2017) - Eker, Sibel; van Daalen, Els; Thissen, Wil
Highlights: Analytical scenario techniques do not explicitly consider stakeholder perspectives. We incorporate stakeholder perspectives into model-based exploratory scenarios. We systematically find the scenario sets that correspond to perspective narratives. We identify the incompatibilities within perspectives and barriers to their envisioned futures. Perspective-specific scenario sets facilitate identifying socially robust policies. Abstract: Several model-based, analytical approaches have been developed recently to deal with the deep uncertainty present in situations for which futures studies are conducted. These approaches focus on covering a wide variety of scenarios and searching for robust strategies. However, they generally do not take the multiplicity of stakeholder perspectives into account in analytic terms, which could bring in diverse opinions and views, not only on possible futures but also on values and interests. In this study, we present an approach to incorporate stakeholder perspectives into model-based scenarios for exploring the future dynamics of the Dutch gas sector. The results demonstrate that the scenario space can be demarcated according to the perspectives. This allows for a systematic comparison of the perspectives and provides a basis for identification of robust strategies. Also, the analysis shows that incompatible elements between the model and perspectives, or within perspectives can be identified. This provides insights about the problem complexity and potential barriers to the futures envisioned by the perspectives. Future research can strengthen this approach by involving stakeholders in modelling and in the model-based representation of the perspective narratives to enhance learning and credibility, and can extend the analysis to identify (socially) robust policies.